Mapping trends and hotspot regarding gut microbiota and host immune response: A bibliometric analysis of global research (2011–2021) - Ni, Zhexin; Wang, Sheng; Li, Yangshuo; Zhou, Ling; Zhai, Dongxia; Xia, Demeng; Yu, Chaoqin (Frontiers in Microbiology, 2022)
Abstract Background: Gut microbiota is a complex ecosystem that is vital for the development and function of the immune system, is closely associated with host immunity, and affects human health and disease. Therefore, the current progress and trends on this field must be explored. Purpose: No bibliometric analysis has been conducted on gut microbiota and host immune response. This study aimed to analyze the current progress and developing trends in this ﬁeld through bibliometric and visual analysis. Methods: Global publications on gut microbiota and host immune response from January 2011 to December 2021 were extracted from the Web of Science (WOS) collection database. GraphPad Prism, VOSviewer software, and CiteSpace were employed to perform a bibliometric and visual study. Results: The number of publications has rapidly increased in the last decade but has declined in the most recent year. Cooperation network shows the United States, Harvard Medical School, and Frontiers in Immunology were the most active country, institute, and journal in this field, respectively. Co-occurrence analysis divided all keywords into four clusters: people, animals, cells, and diseases. The latest keyword within the all clusters was “COVID,” and the most frequently occurring keyword was “SCFA.” Conclusion: Gut microbiota and host immune response remain a research hotspot, and their relation to cancer, CNS disorders, and autoimmune disease has been explored. However, additional studies on gut microbiota must be performed, particularly its association with bacterial strain screening and personalized therapy.